Inhibition of x‐box binding protein 1 reduces tunicamycin‐induced apoptosis in aged murine macrophages. Issue 5 (7th July 2013) - Song, Yang; Shen, Hua; Du, Wei; Goldstein, Daniel R.
Summary: Endoplasmic reticulum (ER) stress is induced by the accumulation of unfolded and misfolded proteins in the ER. Although apoptosis induced by ER stress has been implicated in several aging‐associated diseases, such as atherosclerosis, it is unclear how aging modifies ER stress response in macrophages. To decipher this relationship, we assessed apoptosis in macrophages isolated from young (1.5–2 months) and aged (16–18 months) mice and exposed the cells to the ER stress inducer tunicamycin. We found that aged macrophages exhibited more apoptosis than young macrophages, which was accompanied by reduced activation of phosphorylated inositol‐requiring enzyme‐1 (p‐IRE1α), one of the three key ER stress signal transducers. Reduced gene expression of x‐box binding protein 1 (XBP1), a downstream effector of IRE1α, enhanced p‐IRE1α levels and reduced apoptosis in aged, but not young macrophages treated with tunicamycin. These findings delineate a novel, age‐dependent interaction by which macrophages undergo apoptosis upon ER stress, and suggest an important protective role of IRE1α in aging‐associated ER stress‐induced apoptosis. This novel pathway may not only be important in our understanding of longevity, but may also have important implications for pathogenesis and potential treatment of aging‐associated diseases in general.